1989
DOI: 10.1002/mus.880120207
|View full text |Cite
|
Sign up to set email alerts
|

Recording sound from human skeletal muscle: Technical and physiological aspects

Abstract: In order to examine technical factors that influence muscle sound recording, single twitches of muscle were utilized since their waveforms were likely to be reproducible. We observed that satisfactory recordings could be made with either Archer air interface, or Hewlett-Packard direct contact sensor, microphones. Firm contact and stability between the microphone and the skin surface were particularly important. Frequencies below 20 Hz, the lower limit of the human auditory range, must be recorded, since they a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
106
0
2

Year Published

1996
1996
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(109 citation statements)
references
References 11 publications
1
106
0
2
Order By: Relevance
“…A stabilizing ring, double-sided foam tape, and microporous tape were used to ensure consistent contact pressure of the MMG sensor (Bolton, Parkes, Thompson, Clark, & Sterne, 1989).…”
Section: Methodsmentioning
confidence: 99%
“…A stabilizing ring, double-sided foam tape, and microporous tape were used to ensure consistent contact pressure of the MMG sensor (Bolton, Parkes, Thompson, Clark, & Sterne, 1989).…”
Section: Methodsmentioning
confidence: 99%
“…A stabilizing ring, double-sided foam tape, and microporous tape were used to ensure consistent contact pressure of the MMG sensor. 8 The MMG sensors were removed after the prestretching assessments in preparation for the stretching protocol. The skin was marked where the MMG sensors were placed, so that the sensors could be replaced in the same position after static stretching.…”
Section: Mmg Measurementsmentioning
confidence: 99%
“…Beck et al (2006) compared MMG signals recorded by a piezoelectric contact sensor and an accelerometer during dynamic and isometric torque contraction and found differences between both transducers in terms of amplitude and frequency, and concluded that the MMG transducer may affect the interpretation of MMG signals. Bolton et al (1989) reported that the condenser microphone and the piezoelectric contact sensor show similar frequency response and shape, differing from those shown by the accelerometer . In particular, an accelerometer can be influenced by measurement location (Cescon et al, 2004) and is more strongly affected by movement artifacts than a condenser microphone .…”
Section: ) Graduate School Of Science and Technology Chiba Universimentioning
confidence: 99%